Facile synthesis of rapamycin-peptide conjugates as mTOR and Akt inhibitors. Issue 19 (28th April 2021) - Singh, Shalini; Ali, Rafat; Miyan, Javed; Singh, Varsha; Meena, Sanjeev; Hasanain, Mohammad; Bhadauria, Smrati; Datta, Dipak; Sarkar, Jayanta; Haq, Wahajul
Abstract : An efficient methodology for the synthesis of rapamycin peptide conjugates was developed. Some of these conjugates were found to inhibit the kinase activity of both mTOR and Akt. Abstract : A simple and straightforward process for the synthesis of rapamycin peptide conjugates in a regio and chemoselective manner was developed. The methodology comprises the tagging of chemoselective functionalities to rapamycin and peptides which enables the conjugation of free peptides, without protecting the functionality of the side chain amino acids, in high yield and purity. From this methodology, we successfully conjugate free peptides containing up to 15 amino acids. Rapamycin is also conjugated to the peptides known for inhibiting the kinase activity of Akt protein. These conjugates act as dual target inhibitors and inhibit the kinase activity of both mTOR and Akt.